A COMPARATIVE STUDY BETWEEN MAKE A MATCH AND GROUP INVESTIGATION METHODS ON STUDENTS WRITING COMPLEX SENTENCES ABILITY IN SMP NEGERI 3 PADANGSIMPUAN - ELISSA EVAWANI TAMBUNAN (Institut Pendidikan Tapanuli Selatan, 2018)
The aim of this research is to know whether the result of writing complex sentence ability by using Make a Match method gives a better result than Group Investigation method at the seventh grade students of SMP Negeri 3 Padangsidimpuan. The writer uses an experimental method. The population is the seventh grade students of SMP Negeri 3 Padangsidimpuan, which consisted of 316 students. Two classes, they are VII-1 and VII-2 are taken as two groups of sample by cluster sampling. The whole amount samples is 64 students. The data are collected by using 20 items test as an instrument. The writer uses statistic processes in analyzing data. They are descriptive analysis by using the formula of “t-test”. After calculating the data, it is found that the result of writing complex sentence ability taught by using Make a Match method is categorized “good”. While the students’ writing complex sentence ability taught by using Group Investigation method is categorized “enough”. The result of the analyzed data shows that 2,34 > 2,00 or t-test is greater than t-table. so, the hypothesis is accepted. It means, The Student’s Writing Complex Sentence Ability Taught By Using Make A Match Method is Higher Than Group Investigation Method of the Seventh Grade Students at SMP Negeri 3 Padangsidimpuan